2020
DOI: 10.1101/2020.11.05.369942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling CRISPR gene drives for suppression of invasive rodents

Abstract: Invasive rodent populations pose a threat to biodiversity across the globe. When confronted with these new invaders, native species that evolved independently are often defenseless. CRISPR gene drive systems could provide a solution to this problem by spreading transgenes among invaders that induce population collapse. Such systems might be deployed even where traditional control methods are impractical or prohibitively expensive. Here, we develop a high-fidelity model of an island population of invasive roden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…However, spatially explicit models have indicated that the outcomes of a suppression drive release can be substantially more complicated than those predicted by panmictic population models. In particular, it has been shown that population structure can substantially delay or even prevent complete population suppression for drives with a genetic load high enough to reliably induce population collapse in a panmictic population [11][12][13][14][15] . One mechanism that can prevent population collapse is "chasing", a phenomenon where wild-type individuals recolonize regions where the drive has eliminated the population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, spatially explicit models have indicated that the outcomes of a suppression drive release can be substantially more complicated than those predicted by panmictic population models. In particular, it has been shown that population structure can substantially delay or even prevent complete population suppression for drives with a genetic load high enough to reliably induce population collapse in a panmictic population [11][12][13][14][15] . One mechanism that can prevent population collapse is "chasing", a phenomenon where wild-type individuals recolonize regions where the drive has eliminated the population.…”
Section: Introductionmentioning
confidence: 99%
“…In this manner, drive and wild-type alleles can persist indefinitely, following a chaotic pattern of local suppression and recolonization. This chasing phenomenon seems to be a common feature of spatial models for many types of suppression drive, regardless of whether the model is implemented using abstract spatial patches 14 , networks of linked demes of mosquito populations 12,13 , or continuous space with discrete generations 11,15 . Unlike panmictic models, these spatial models predict that even modest differences in efficiency between drives can potentially have large effects on the outcome of a drive release, meriting careful consideration of drive candidates to identify those with the greatest potential for success in realistic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The trade‐off, however, is an increased risk of effects on nontarget populations in the event of a gene drive escape due to a higher frequency of susceptible alleles. While the gene drive is expected to rapidly be eliminated in such a scenario due to the presence of resistance alleles (Champer, Oakes, et al, 2020; Sudweeks et al, 2019), transient nontarget population impacts or even the public perception of increased risk of spread might prove unacceptable. Filtering LFA based on an intermediate “source” population allele frequency (≤0.50) resulted in a small number of sites, though several showed potential for multiplexed gRNA and occurred in genes of interest, and may therefore represent a reasonable compromise.…”
Section: Discussionmentioning
confidence: 99%
“…High-quality annotated reference genomes are required to identify target genes and enable comprehensive evaluation of the effects of existing variation on gene drive efficiency. These data can then inform predictive models assessing the effectiveness of specific gene drive systems in target populations under variable conditions (including environmental change and conservation management; Champer et al, 2020). Further, gene drive trials must be carefully designed to be representative of real-world impacts, as there may be differences in implementation and effects between captive laboratory populations and wild populations due to local behavioural adaptation or other indirect ecological effects (Mazza et al, 2020;Russell et al, 2009;Tompkins & Veltman, 2006).…”
Section: Gene Editingmentioning
confidence: 99%